An exploration of gut microbiota mechanisms underlying differential efficacy of vitamin D supplementation in children associated with lipid metabolism - Wang, Hui; Liu, Wan-ying; Wang, Tong-tong; Yu, Ying-tan; Li, Xin-xu; Zhang, Fei-tong; Zhang, Chen-yang; Tong, Xiao (Frontiers in Nutrition, 2025)
IntroductionVitamin D plays an indispensable role in children’s growth. Although there has been a growing recognition of the importance of vitamin D supplementation, its deficiency remains a prevalent global issue. This deficiency is frequently associated with abnormalities in lipid metabolism, which can impede the normal development of children. In recent years, the gut microbiota, which exerts a significant influence on drug metabolism and nutrient absorption, has captured increasing attention. This study explores gut microbiota mechanisms underlying the differential efficacy of vitamin D supplementation related to lipid metabolism, offering references for clinical problem-solving.MethodsA retrospective analysis of 2,307 pediatric patients examined serum vitamin D levels and their correlation with lipid metabolism. To explore the potential mechanism, children with vitamin D deficiency underwent a 3-month supplementation and 1 h of outdoor activities each day. Then, 24 subjects were selected (12 poor and 12 good responders to supplementation). 16S rRNA sequencing was used to analyze gut microbiota composition to find differential microbiota, and PICRUSt2 was used for functional prediction to identify potential metabolic differences.ResultsOur study revealed a widespread prevalence of vitamin D insufficiency or deficiency among children. Moreover, a negative correlation was established between vitamin D levels and lipid metabolism. The results of 16S rRNA sequencing indicated that Agathobacter emerged as the key gut microbiota influencing the efficacy of vitamin D supplementation. Its abundance was negatively correlated with lipid metabolism. Through PICRUSt2 analysis, distinct ‘other carbohydrate degradation’ pathways were identified in children with different responses to vitamin D supplementation.DiscussionThis study confirms the widespread occurrence of vitamin D insufficiency or deficiency in children, which is negatively correlated with lipid metabolism. Agathobacter may influence vitamin D absorption and lipid metabolism through the ‘other carbohydrate degradation’ pathway. Our findings offer more insights for clinical problem-solving and new therapies based on child–gut microbiota interactions.